Children friendly masjid: a glimpse on jamaah’s perceptions towards children at masjid - Abu Bakar, Aniza; Zulkifely, Zur Atiqa; Mohd Bohori, Nur Ayuni (IIUM Press, International Islamic University Malaysia, 2020)
The role of the masjid was diverse during the era of the Prophet Muhammad SAW, and it continued for decades by his (SAW) companions and the following caliphs. The diverseness of masjid's role reflected the people that were being served by this institution and reflected the criteria of inclusiveness. As time goes by and as the government developed, various ministries were established. This establishment witnessed the taking over of various roles by masjid to the people by these ministries and their agencies. Thus, masjid seems to be seen as a sacred place to perform specific ibadah and that it should pose a tranquil environment to the effect that children may not be welcome as they are seen as the 'agent' that 'disrupt' the tranquillity and sacredness of masjid. This initial study is carried out to identify the public's perception towards the presence of children at the masjid. An online survey form was distributed via the social media that is the WhatsApp application to various groups established by the administration of Masjid Al Ridhuan, Hulu Kelang. Based on the response of 90 respondents, the result reveals the excellent level of acceptance of children at masjid among the jamaah. They also provided their opinion on the spaces where they felt would be suitable for children based on their age range. Children between the age of 7 to 9 years old seemed to be well accepted in the main prayer hall while the rest are perceived to be more suitable to be at other sub-spaces of the masjid.